Influence of polyurethane dispersion as surface treatment on mechanical, thermal and dynamic mechanical properties of laminated woven carbon-fiber-reinforced polyamide 6 composites. (1st March 2019) - Zhao, Defang; Hamada, Hiroyuki; Yang, Yuqiu
Abstract: Carbon fiber (CF) plain-woven fabric-reinforced polyamide 6 (PA6) (CF/PA6) laminates were fabricated by the hot-compression technique. The carbon plain woven was treated with polyurethane dispersion (PUD) to improve the compatibility and adhesion with PA6, and the effects of PUD treatment on the mechanical, thermal and dynamic mechanical properties of the composites were investigated. The results of flexural tests and low-cycle flexural fatigue tests demonstrate that compared with a composite without PUD treatment, treated CF/PA6 laminates (the pick-up ratio of PUD is 0.53%) not only exhibit a 28.6% enhancement in flexural strength but also acquire a 5.4% improvement in residual flexural strength retention after fatigue tests. The additional oxygen-containing groups (e.g. CO) that are associated with PUD treatment are the contributing factors that strengthen the interfacial interactions between the CF and PA6 matrix, as supported by Fourier transform infrared spectroscopy results. Morphological analyses of the fracture surfaces using optical microscopy and scanning electron microscopy reveal an improvement in interfacial adhesion between the CF and PA6 matrix in the presence of PUD treatment. Differential scanning calorimetry results reveal that PUD treatment leads to a decline in the percentage of crystallinity (Xc ). The storage modulus and glass transition temperature (Tg ) of this composite with PUD treatment show an impressive improvement compared with the virgin composite whereas the damping coefficient (tan δ) decreases according to dynamic mechanical analysis results. Moreover, this composite also demonstrates improved thermal stability in comparison with untreated CF/PA6 laminates.